Al-Ani, Nizar Sa’id. “Crisis in the Theory, Sources of Knowledge, Methodology, and Standards of Contemporary Psychology,” Year 6, Issue 22 (Fall 1421 AH/ 2000 CE), Pp. 35-61. - العاني, نزار سعيد (Al-Fikr al-islāmī al-muʿāṣir (previously Islamiyat al-Ma'rifah), 2000)
After an introduction on the crisis of contemporary psychology, Nizar al-Ani’s article explains psychological theories and their development, describing the five sources of knowledge in psychology: feeling or general senses, reliance on the authority or specialization, causation, unorganized observation, and the scientific method (which consists of description, prediction, control, and explanation). He then collects and interprets data, analyzing the descriptive, relational, and experimental research. He addresses the standards and criterions, and explains deviation, ill-conditioning, and personal misery, citing the views of Atkinson, Feldman, Barlow, Durand, Effranques, Wightn, Kass, Kirk, Rosenhan, and others.